Preliminary Assessment of a Novel OTEC CWP Design using Sand-Filled Sandwich Pipe - Al Kautsar Hensa Akbar; Adiputra Ristiyanto; Kusharjanta Bambang; Prabowo Aditya Rio; Carvalho Hermes (E3S Web of Conferences)
Ocean Thermal Energy Conversion (OTEC) is a renewable energy source that utilizes the temperature difference between warm ocean surface water and cold deep ocean. This technology offers excellent potential as a sustainable solution to the global energy crisis. One of the critical components in OTEC is the Cold-Water Pipe (CWP), which is essential in delivering deep seawater to the thermal system. This study offers a new flexural test in the form of a sandwich pipe made of sand, which is lightweight and capable of damping vibration as an infill to evaluate its characteristics. The benchmarking phase was conducted to validate the test procedure used. the case study focused on geometry variation, a parameter that significantly affects the flexural strength of the structure. significant effect on the flexural strength of the pipe, so variations to the geometry parameter were selected as the main case study. the test results showed that a larger diameter increases the stability of the pipe, as shown by the D50 specimen having a higher ultimate bending moment value than D25. The variation of CWP geometry significantly affected its performance.